Study on Contact Stress Distribution of Single Tooth Meshing Dangerous Area of Heavy Load Gear - Yao Jun (Jixie chuandong)
Aiming at the large-modulus and special-weight heavy-duty gears,the gear contact stress analysis model is established to study the contact characteristics of the tooth surface during the meshing process.By using the two methods of Abaqus finite element software analysis and Hertz contact stress calculation,the contact stress distribution law of dangerous area under the meshing condition of the heavy load gear is found,the contact stress distribution of contact teeth is given by computer simulation. The results show that the maximum value of the contact stress occurs at the contact surface of the tooth surface and along the tooth. The contact stress occurs on the driving wheel,the contact stress is linearly distributed along the tooth width direction,the tooth width is too large,resulting in the uneven load of the tooth to the load,and the contact stress occurs in the direction of the tooth. Therefore,by increasing of the drive wheel strength and using the positive displacement,it is useful for improving the reliability and service life of heavy equipment.